How to Strengthen Hungarian Small enterprises that face the challenges of neo-globalization - Árva, László; Csath, Magdolna; Giday, András (Public Finance Quarterly, 2023)
In our article we have analysed the problem, how can the small enterprises (SME-s) survive in the shadow of the transnational companies (TNCs). Besides analysing the historical process of globalization, and its latest form, the 'neo-globalization', we were mainly focusing on wage levels. Local small enterprises generally are not able to increase their prices and their wages, but on the other hand, transnational companies – in case of necessities, for e.g. labour shortage -, can easily pay higher wages for their workers, as transnational companies are realizing extra profits due to their specific business model. TNCs have their products produced in poorer, low wage periphery countries, and then these products are sold in the rich centrum countries at higher prices, creating huge and easy extra profits. In this globalized model, TNCs are interested to maintain income differences between periphery and centrum regions. That is why we are convinced that governments should help small and medium companies, which are producing for the local markets. Naturally, later those SME-s may be able to move to international markets as well. Our final conclusion is that social security payments and special SME credits, which are tied to company sizes are not distorting the market, but rather are rebalancing an already distorted market structure.